King & Kayla and the case of found Fred - Butler, Dori Hillestad (Butler, Dori Hillestad. King & Kayla., 2019)
Trying to communicate with his human owner (and detective partner) can be frustrating for King the golden retriever as he uncovers clues in a missing dog case.